PECULIARITIES OF THE FREQUENCY AND CLINICAL MANIFESTATIONS OF CONGENITAL HEART DEFECTS IN CHILDREN DURING THE COVID-19 PANDEMIC - Badieva Dilorom Saidovna (Web of Journals Publishing, 2025)
The COVID-19 pandemic has significantly affected healthcare systems worldwide, leading to changes in the detection, clinical presentation, and treatment of congenital heart defects (CHDs) in children. This study aims to analyze the frequency and clinical features of CHDs during the pandemic period, comparing them with pre-pandemic data.
Keywords: Congenital heart defects, COVID-19, children, clinical manifestations, frequency, pandemic.